2015
DOI: 10.1371/journal.pgen.1005053
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype Specific Analyses Reveal Distinct Regulatory Mechanism for Chronically Activated p53

Abstract: The downstream functions of the DNA binding tumor suppressor p53 vary depending on the cellular context, and persistent p53 activation has recently been implicated in tumor suppression and senescence. However, genome-wide information about p53-target gene regulation has been derived mostly from acute genotoxic conditions. Using ChIP-seq and expression data, we have found distinct p53 binding profiles between acutely activated (through DNA damage) and chronically activated (in senescent or pro-apoptotic conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 88 publications
(117 reference statements)
1
54
0
1
Order By: Relevance
“…No p53 targets were detected in the marker genes of the other five clusters in Figure 1C (see Table S1).
Figure 2Age-Specific Cluster Carries Signature of Pro-proliferative and Anti-proliferative Stimuli(A) Manual annotation of top 20 marker genes with Ras senescence (RIS), apoptosis (Kirschner et al., 2015), and pStat3 and pStat5 datasets (Lau et al., 2015). Red indicates p53, and green indicates pStat targets.(B) KEGG pathway analysis of marker genes for old-specific cluster.
…”
Section: Resultsmentioning
confidence: 99%
“…No p53 targets were detected in the marker genes of the other five clusters in Figure 1C (see Table S1).
Figure 2Age-Specific Cluster Carries Signature of Pro-proliferative and Anti-proliferative Stimuli(A) Manual annotation of top 20 marker genes with Ras senescence (RIS), apoptosis (Kirschner et al., 2015), and pStat3 and pStat5 datasets (Lau et al., 2015). Red indicates p53, and green indicates pStat targets.(B) KEGG pathway analysis of marker genes for old-specific cluster.
…”
Section: Resultsmentioning
confidence: 99%
“…The underlying mechanism includes an altered cytokine secretion and malignant stem cell activation which is regulated by CDK6 in a largely kinase-independent manner. Moreover, apoptotic players are regulated by CDK6 (e.g., B-cell translocation gene 2 (Btg2) [61], phorbol-12-myristate-13-acetate-induced protein 1 (Pmaip1) [62], krueppel-like factor 6 (Klf6) [63,64], activating transcription factor 3 (Atf3) [61,64,65]) and JAK2-V617F + purified Lineage − Sca1 + cKit+ (LSK) cells lacking CDK6 show enhanced apoptosis. CDK6-deficient LSK cells display altered expression of several negative regulators of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signaling (e.g., NF-κB inhibitor zeta (NFκBiz), suppressor of cytokine signaling 3 (Socs3) [66][67][68][69]).…”
Section: Cdk6 Acts Largely Kinase-independent In Jak2-v617f + Hscsmentioning
confidence: 99%
“…In contrast, p53 is involved in wider stress responsive contexts, including cell cycle, acute DDR and DNA repair, apoptosis, and metabolism (Levine & Oren 2009). Interestingly, it has recently been shown that chronic activation of p53, such as seen in senescence, drives a distinct transcriptional program to that seen in the acute p53 activation, upon DDR (see sidebar) (Kirschner et al 2015). In addition, p53 has a range of different functions within the senescence context (Johmura & Nakanishi 2016, Rufini et al 2013.…”
Section: The Senescence Networkmentioning
confidence: 99%